2019
DOI: 10.1371/journal.ppat.1007634
|View full text |Cite
|
Sign up to set email alerts
|

The ETS transcription factor ELF1 regulates a broadly antiviral program distinct from the type I interferon response

Abstract: Induction of vast transcriptional programs is a central event of innate host responses to viral infections. Here we report a transcriptional program with potent antiviral activity, driven by E74-like ETS transcription factor 1 (ELF1). Using microscopy to quantify viral infection over time, we found that ELF1 inhibits eight diverse RNA and DNA viruses after multi-cycle replication. Elf1 deficiency results in enhanced susceptibility to influenza A virus infections in mice. ELF1 does not feed-forward to induce in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 77 publications
2
64
0
Order By: Relevance
“…Finally, the transcription factor ELF1 was also found to affect viral entry. ELF1 governs a complex transcriptional program of over 300 genes that are largely distinct from those induced by IFN, suggesting that a secondary antiviral transcriptional cascade acts to inhibit SARS-CoV-2 entry, and potentially other stages of the viral life cycle (Seifert et al, 2019).…”
Section: Restriction Of Sars-cov-2 Entrymentioning
confidence: 99%
“…Finally, the transcription factor ELF1 was also found to affect viral entry. ELF1 governs a complex transcriptional program of over 300 genes that are largely distinct from those induced by IFN, suggesting that a secondary antiviral transcriptional cascade acts to inhibit SARS-CoV-2 entry, and potentially other stages of the viral life cycle (Seifert et al, 2019).…”
Section: Restriction Of Sars-cov-2 Entrymentioning
confidence: 99%
“…While a number of reports have documented non-canonical activation or delayed stimulation of subsets of ISGs during viral infection, the molecular pathways that can control these subsets of ISGs are not well understood (Pulit-Penaloza et al, 2012;Rose et al, 2010). However, a number of studies have identified transcriptional regulators of subsets of ISGs (Froggatt et al, 2019;Perwitasari et al, 2011;Seifert et al, 2019), and the mRNA Cap1 methyltransferase CMTR1 was recently shown to regulate the expression of certain ISGs (Williams et al, 2020). These studies demonstrate the complexity of regulation of expression of ISGs that extends beyond transcriptional induction of ISGs from signaling of the JAK-STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, our overall understanding of posttranscriptional regulation of ISG expression is still emerging. Additionally, while a number of studies have identified subsets of ISGs that have unique transcriptional regulators, other mechanisms that govern the regulation of subclasses of ISGs have not been well characterized (Froggatt et al, 2019;Perwitasari et al, 2011;Seifert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ETV7 is induced as an ISG and is repressive, whereas most ETS transcription factors are activators, including ETS transcription factors recognized to assist in the induction of ISG expression (e.g. ELF1 (25), PU.1 (71)). We also found repeatedly in our work that the reporters and genes impacted by ETV7 contained ETS sites within ISRE sequences ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon responsive factors (IRFs) 1 and 7 are ISGs and transcription factors that activate subsets of ISGs (23,24). Further, recent work has shown that ELF1 (E74-like ETS transcription factor) is induced by IFN and facilitates the expression of a group of genes not otherwise activated by the IFN response (25). Additional regulatory steps for ISGs, post-JAK/STAT signaling, likely exist to allow the cell to fine-tune its antiviral activity for an effective and appropriate response.…”
Section: Introductionmentioning
confidence: 99%